La Distancia Mínima Entre Taladros Para Evitar Los Daños De Los Detonadores Electrónicos Por Presion Dinámica, En Mina Lagunas Norte - Benites Correa, Agapito Gabriel (2017)
The electronic blast because of its greater precision, nowadays practically covers the whole of the Great Mining. Electronic detonators have several protections against external effects such as dynamic pressure. They allow to qualify as the detonator with the highest dynamic pressure resistance in the market. However, if conditions exceed established resistance values there is always a possibility of failure. The rate of dynamic pressure events at the level of Latin America in the years 2014 - 2015 to date is 1.7 ppm. As a result of the finding of an armed premium with its electronic and nonelectric detonators, associated to the drill No. BF 43 of the mesh P12 4040 174, on July 28, 2016 in the Dafne area began the execution of a series of corrective and preventive measures derived from the investigation carried out by the finding of a booster not started in the material flown, which contained two detonators (one electronic and another non-electric) with obvious physical damage. During the investigation of the event, it was pointed to the dynamic pressure as a potential cause of the event; however, sufficient implementation information was not available to confirm or discard this hypothesis. This research aims to define critical distances between drills for different scenarios, based on the strength of the aluminum and copper capsules, drill diameter, load length and density of the explosive, to avoid the mechanical failure of the detonators due to dynamic pressures. For that, tests were carried out in three sectors: Volcanic, Morrenas and Andesite, during September and October, along with blasting according to the mining plan of the mine. The field information was used to determine the dynamic pressures of the detonators which, through analysis and adjustment of dynamic pressure from the recorded VOD and the density of the explosive, generating a distance attenuation equation using an exponential regression model, for the rocky massif present in the study area. It was possible to determine an average of critical distances in order to ensure the correct functioning of electric detonators (3 meters) The results obtained are only representative of the Dafne, Josefa zone and it is advisable to carry out a new study of vibration measurement in case of wanting to determine possible effects of dynamic pressure in some other sector of the mine.